Penerapan Konsep Zen Perencanaan Dan Perancangan Senior Living Kelas Premium Untuk Lansia Di Tegalalang, Ubud: Indonesia - Gede Andika Pramana Putra; I Nyoman Gede Maha Putra; Made Anggita Wahyudi Linggasani (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
Planning and Design of Premium Class Senior Living in Tegalalang, Ubud is a residence for the elderly with an age limit in Tegalalang, Ubud. Senior living is aimed at seniors aged 45-54 years who want to spend their time in peace and away from the noise. Besides that, senior living with good facilities can support to provide a sense of security and comfort based on what they need. Other facilities in senior living like a spa/salon, counseling, yoga, and a gym. This senior living is located in Tegalalang, Ubud which is far from noise, a safe and calm atmosphere, and a green area for the psychological influence of the elderly. The methods used in the Planning and Design of Premium Class Senior Living in Tegalalang, Ubud are data collection methods, data presentation methods, and data analysis methods. The architectural approach used in senior living is anthropometric architecture with a base concept it is Zen, besides that the design theme used is contemporary tropical architecture which aims to unite simplicity, naturalness, and keep up with current developments so as to further increase the interest of the elderly to follow activities and living in this senior living.